LOW BIRTH WEIGHT IS A RISK FACTOR OF MALNUTRITION IN CHILDREN UNDER FIVE YEARS OLD IN COASTAL AREAS - Saimin, Juminten; Nugraha, Ahmad Fahmi; Asmarani, Asmarani; Ashaeryanto, Ashaeryanto (Public Health of Indonesia, 2019)
Background: Malnutrition is a public health problem, especially in developing countries. Malnutrition of children can affect brain development during growth and increase morbidity and mortality. Low birth weight (LBW) plays an important role in child morbidity and mortality. The prevalence of malnutrition in children under five years old and LBW in Indonesia are still high.Objective: This study aimed to assess the risk of LBW on the incidence of malnutrition in children under five years old in coastal areas.Method: This was an observational analytic study with case control approach. The study was conducted on 64 respondents in the coastal area of Kendari City, Southeast Sulawesi on November to December 2018. Case group (n=16) was children under five years old who experienced malnutrition in the working area of Abeli, Mata and Benu-Benua Health Center in October 2018. Control group (n=48) was taken by measuring body weight and then adjusted to the category and threshold of nutritional status based on the body weight index according to age. Sixteen respondents of case group were recruited using total sampling. Forty-eight respondents of control group were also recruited using purposive sampling with non-matching method according to the inclusion and exclusion criteria. The Odd Ratio (OR) statistical test was used with a 2x2 contingency table and a 95% confidence level with a significance level of Î± = 0.05.Results: The majority of respondents were 25-48 months old, and maternal age was mostly 36-45 years old in the case group (37.5%) and 26-35 years old in the control group (50.0%). The majority of maternal education level was junior high school in the case group (43.7%) and high school in the control group (47.9%). The statistical test results were obtained OR = 5.923 (CI=95%) with Lower Limit (1.724) and Upper Limit (20.346).  Conclusion: Infants with LBW had a 5 times higher risk for experiencing malnutrition in childhood in coastal areas. Therefore, knowledge of LBW and malnutrition is needed to improve public health status.